PELATIHAN PEMBUATAN PUDING DAUN BINAHONG BAGI IBU-IBU PKK DESA PAGERTOYO KECAMATAN LIMBANGAN KABUPATEN KENDAL - Puspitasari, Anita Dwi; Pertiwi, Siti Maisyaroh Bakti; Nugroho, Rahmadinda Maharani; Putri, Galuh Lukita (WIDHARMA - Jurnal Pengabdian Widya Dharma, 2024)
Pagertoyo Village, Limbangan District, Kendal Regency is one of the villages that has the potential for growth and development of herbal plants. One of them is the binahong plant (Anredera cordifolia). This plant has the property of curing various diseases, including lowering blood pressure and gout. This community service aims to provide education about the benefits of the binahong plant and training in making binahong pudding to PKK women in Pagertoyo Village, Limbangan District, Kendal Regency. Implementation of activities was carried out in 3 stages. The first stage is a health check (check blood pressure and uric acid). The second stage is education about the benefits of the binahong plant. The participants were given a lecture about the benefits of the binahong plant followed by a discussion and question and answer session. The third stage is training in making binahong pudding. The implementation of this community service activity ran smoothly and successfully. The participants actively participated in question-and-answer sessions and discussions as well as training.